PENGARUH PERTUMBUHAN TANAMAN KANGKUNG DENGAN MEMANFAATKAN LIMBAH PADAT AMPAS TAHU SEBAGAI PUPUK ORGANIK - Paskalius Apriyanto Merahabia; Batseba E.L.L. Gomies; Jacob J. Lawalata; Mery I.A. Linggi; Antipas Senidomen (STIPER Santo Thomas Aquinas Jayapura, 2026)
Water spinach (Ipomoea reptans Poir) is a short-term vegetable plant that can grow and develop in various environments. The purpose of this study was to obtain information about the effect of tofu dregs solid waste on the growth of water spinach plants. The study was conducted in Kemiri, Jayapura Regency, for 1 month, namely, from October to November 2025. This study used a Randomized Block Design (RAK) with 6 treatments of tofu dregs solid waste, namely, (A0) = control (A1) = 100 gr of tofu dregs solid waste (A2) = 150 gr of tofu dregs solid waste (A3) = 200 gr of tofu dregs solid waste (A4) = 250 gr of tofu dregs solid waste (A5) = 300 gr of tofu dregs solid waste, the treatment was repeated three times so that there were 18 experimental units. Each repeated treatment was planted with 5 polybags so that 90 polybags were obtained. Research Variables Plant height (Cm), Number of leaves, Root length Fresh weight. The data obtained from the research results were analyzed using a randomized block design following Petersen (1994). The results showed no significant effect on the variables of plant height, number of leaves, root length and fresh weight of plants. The A2 treatment given can increase the growth of the highest plant height compared to treatments A0, A1, A3, A4, and A5, while the A3 treatment can increase the number of leaves, root length, and fresh weight of plants but is not statistically significantly different.